Kepastian Dan Perbandingan Hukum Mengenai Saham Pinjam Nama Atau Nominee Shareholder Antara Indonesia Dan Thailand - Dipadary Abiyudara (Universitas Islam Indonesia, 2020)
The purpose of this study is to examine the legal certainty of nominee shareholder in Indonesia and the legal comparison between Indonesia and Thailand. This is a normative legal research with statutory and comparative approaches. The results of this study are first, the nominee shareholder violates 6 Indonesian laws, especially the articles in UUPM No. 25 of 2007, UUPT No. 40 of 2007, and the Civil Code. Second, there are 3 driving factors for nominee shareholders, namely the presence of foreign intentions to control state assets, the complexity of licensing foreign investment, and tax issues. Third, a comparative analysis of the UUPM, UUPT, and the RI BKPM Regulation No. 1 of 2020 with the Thailand Foreign Business Act 1999 found that Thailand imposes more severe and stricter criminal sanctions and supervisory policies than Indonesia. Indonesian law still provides loopholes for nominee practice.